A market study on the effectiveness of Diploma Of Art And Design, Industrial Design (DIDE) programme towards students’ early academic and career development / Nurul ‘Ayn Ahmad Sayuti...[et al.] - Ahmad Sayuti, Nurul ‘Ayn; Md Hashim, Azhari; Abdul Karim, Izza Syahida; Hasan, Asrol; Mamat Nawi, Azmir; Yusoff, Fadila (2018)
undergraduates and postgraduates study in Malaysia. In 2000, UiTM introduced the Diploma Programmes offering to ‘Sijil Peperiksaan Malaysia’ SPM holders. The Diploma Programmes served as a platform for Bumiputera students to further their higher academic education and prepare them for the professional careers in the field of science and technology, social sciences and humanities, and business and management. The academic programme of Industrial Design is one of the areas introduced under the Faculty of Art and Design since the early development of ITM before UiTM. This programme is offered for almost 50 years, in line with the industries demand. In search of the relevancy of the programme offered, a market survey and interviews were conducted involving alumni and industry expertise in this study. The results indicated the current DIDE programme curriculum is relevant and matches with the industrial needs. This study suggests for the DIDE programme to be updated with the current needs and the results lend further weight, will improve and strengthen the curriculum design.